Exploration of Canva as a Creative Solution in Creating Visual Learning Media to Develop Learning Interest of 4-5 Years Old Children at Tunas Bakti Kindergarten - Banuvita, Rellive Enka; Fauziyah, Nur (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to describe the role of canva-based visual learning media in increasing the learning interest of 4-5 years old children in Tunas Bakti Kin-dergarten. Methodology: This study uses a qualitative descriptive method. The research subjects con-sisted of teachers and children aged 4-5 years at Tunas Bakti Kindergarten who were involved in learning activities. Data were collected through inter-views, observations and documentation. Results: Canva-based visual learning media was able to significantly increase the learning interest and engagement of 4-5-year-olds in the learning process. With its attractive and interactive design, Canva is able to change the dynam-ics of learning at Tunas Bakti Kindergarten. Children who initially had a low interest in learning and often felt bored showed increased focus and enthusi-asm for learning activities. In addition, participation that was previously pas-sive has transformed into more active, where children interact more, both with teachers and peers. Applications/Originality/Value: This research is useful in utilizing Canva as a creative solution for visual learning media, in order to increase the learning interest of 4-5 years old children. The results support educators in creating more interesting and ap-propriate materials for children's development while improving teachers' competence in utilizing technology as part of the learning process.